2003
DOI: 10.1093/rheumatology/keh012
|View full text |Cite
|
Sign up to set email alerts
|

Lupus nephritis: treatment with mycophenolate mofetil

Abstract: MMF appears to be an efficacious and safe treatment in patients with proliferative forms of lupus nephritis who do not respond to or cannot tolerate conventional treatment. The efficacy of MMF in lupus membranous nephropathy remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 16 publications
2
62
1
4
Order By: Relevance
“…Recently, MMF has been introduced in the treatment of SLE, with a significant therapeutic benefit and relative minor side effects [5,6,7,8,9,10,11,12]. Due to its potential therapeutic effects, it is previewed that in the near future, following head-to-head studies with conventional treatment, MMF administration will further increase and more SLE patients will be exposed to MMF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, MMF has been introduced in the treatment of SLE, with a significant therapeutic benefit and relative minor side effects [5,6,7,8,9,10,11,12]. Due to its potential therapeutic effects, it is previewed that in the near future, following head-to-head studies with conventional treatment, MMF administration will further increase and more SLE patients will be exposed to MMF.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been introduced in the treatment of autoimmune diseases, including rheumatoid arthritis [2], systemic vasculitis [3], autoimmune hemolytic anemia [4] and SLE [5,6,7,8,9,10]. At this date, MMF is considered a safe and effective alternative therapy for renal and extrarenal manifestations in SLE not responding to a conventional treatment [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Dooley et al reported improvements in proteinuria and renal function with MMF in 12 patients who were either resistant or relapsed after treatment with cyclophosphamide (17). In a retrospective study by Kapitsinou et al, 10 of 14 patients with proliferative LN who previously received cyclophosphamide were treated with MMF and went into complete remission, whereas the other 4 patients had partial remission with improved renal function and degree of proteinuria (19). In another study by Kingdon et al, MMF did not significantly reduce proteinuria in 13 patients who had relapsed despite conventional therapy (or were unable to receive alkylating agents); however, there was a reduction in the rate of decline of renal function along with improvement in serologic markers (18).…”
Section: Switch From Cyclophosphamide To Mmf or Vice Versamentioning
confidence: 99%
“…The most frequent side effects of MMF are infections and gastrointestinal intolerance, which occur in about one-third of all patients (19,21). These adverse effects are usually mild and discontinuation of the drug is often not required.…”
Section: Switch From Cyclophosphamide To Mmf or Vice Versamentioning
confidence: 99%
“…Furthermore, this favorable profile has been observed in patients with renal impairment [5,6,7]. Although no randomized clinical trials have been performed in patients with CYC-refractory and relapsing LN, several reports and small cases series have shown that MF is highly effective and well tolerated and that it could be a good alternative in patients with LN [8,9,10]. Therefore, the role of MF in refractory and relapsing LN and its association with baseline clinical and analytical data is worth investigating.…”
Section: Introductionmentioning
confidence: 99%